Analisis Kinerja Kombinasi Sistem CDMA-OFDM dengan MIMO - Awirya, Valen; Sukiswo, Sukiswo; Zahra, Ajub Ajulian (Transmisi, 2010)
Wireless transmission system is hampered by a condition that causes multipath channel fading at the receiver. It required transmission technologies that are resistant to multipath channel conditions. One is multiple access technology combination of OFDM and CDMA. To further increase the interference immunity of signal channel is carried out in combination with the MIMO antenna diversity technology.  This final project is to make simulation of multiple access technologies CDMA-OFDM combined with MIMO. The parameters varied are the number of the receiving antenna and the speed of the user. Channel used is the Rayleigh channel and Additive White Gaussian Noise (AWGN). The performance of the system can be measured Bit Error Rate (BER) compared to the value of Eb / No. Performance of 2x5 MIMO system with the speed of the user 5 km/h produces Eb/No 3 dB lower than 2x3 MIMO and 1,5 dB lower than 2x4 MIMO to achieve the target BER 10-3. Performance of 2x5 MIMO system with the speed of the user 40 km/h produces Eb / No 4 dB lower than 2x3 MIMO and 1 dB lower than 2x4 MIMO to achieve the target BER 10-3. At speeds of 80 km /h, the performance of MIMO  CDMA -OFDM system worst found on 2x3 MIMO scheme, the target BER 10-3 can not be fulfilled on the value of Eb/No = 30. 2x4 and 2x5 schemes provide better performance with a value of Eb/No of 8 dB and 4 dB to achieve the target BER.The increase in user speed degrade the performance of MIMO CDMA -OFDM system. With 2x5 MIMO scheme on the user speed 5 km / h, the target BER 10-3 is reached on the value of Eb/No of about 1 dB. While at the speed of 40 km / h and 80 km/h achieved at Eb/No value of about 2 dB and 4 dB. Keyword :   CDMA, OFDM, MIMO, Rayleigh, AWGN